(untitled) (Research, Society and Development, 2022)
The present paper makes an analysis of the frequency of sky conditions in the city of Maputo/Mozambique based on the clearness index (Kt). From the determination of extraterrestrial solar radiation and measured data of four years of global daily radiation, Kt was calculated. Different sky conditions were classified according to the Escobedo criterion, which dispenses the data of direct and / or diffuse radiation in its classification. The city of Maputo, during the year, is observed more days with conditions of clear sky, in average of 120 days. And for cloudy sky conditions, the city of Maputo presents the least number of days, with an average of 48 days. The frequency of days for partially cloudy sky and partially clear sky conditions is 85 and 112 days respectively. The information generated in this paper can be used in future studies to project solar systems for thermal use or direct conversion of solar radiation into electricity.